Adopting interoperability solutions for online tourism distribution: An evaluation framework. (1st February 2016) - Reino, Sofia; Alzua-Sorzabal, Aurkene; Baggio, Rodolfo
Abstract : Purpose: – The purpose of this study is to identify the factors that make the adoption of interoperability solutions for online tourism distribution (OTD) more likely by small operators and to develop an evaluation framework for this solutions. Research identifying these determinants is missing. The resulting evaluation framework is then applied to evaluate a number of extant technological solutions focused on interoperability solutions for OTD. Design/methodology/approach: – In an attempt to address this gap of research, this paper undertakes a series of interviews and focus groups of the European tourism industry. Findings: – Findings partly aligned with the suggestion made by previous research about technology adoption by micro, small and medium tourism enterprises (SMTEs), they also highlighted some issues which are specific to the adoption of interoperability solutions for OTD. These related to the scarcity of information and communication technology (ICT) applications specifically designed for mini and micro enterprises, the very limited capabilities available for using efficiently ICTs in business-to-business (B2B) operations and the difficulty in collaborating with other companies due to the number of different solutions used in the industry, especially when dealing with large aggregators (global distribution systems (GDSs) or large online travel agencies) and lack of standardization for data. Research limitations/implications: – The study has important theoretical implications. It provides a better understanding of issues affecting the adoption of interoperability solutions for OTD by SMTEs, such as the scarcity of ICT applications specifically designed for mini and micro enterprises, the very limited capabilities available for using ICTs efficiently in B2B operations and lack of standardization. Practical implications: – It facilitates making decisions about adopting interoperability solutions for online distribution solutions, both by suppliers and destination managers. Originality/value: – Limited work has focused on understanding issues affecting the adoption of interoperability solutions for OTD solutions among SMTEs.